Dynamics of education policy formulation after the 18th amendment in Province of Khyber Pakhtunkhwa, Pakistan - Ahmad, Zaheer; Shah, Ikram; Alam, Arif; Khan, Humayun (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
The 18th Amendment to the Constitution of Pakistan has authorized provinces, including Khyber Pakhtunkhwa (KPK), to formulated autonomous education policies. This authority includes determining the direction and strategy of the education system for future goals such as literacy rates, gender equality, and quality education. However, after 14 years of implementing this decentralization, KPK's progress in educational policy autonomy has been inadequate. This study evaluates the performance of Khyber Pakhtunkhwa Province in formulating its own educational policies in the context of the post-18th Constitutional Amendment era. This research is based on semi-structured interviews conducted with key stakeholders in the province. The study also found that as a small province, KPK faces various challenges, such as a shortage of experts in education policy formulation, limited financial and human resources, political interference, an unbalanced federal system, and a lack of extensive consultation with stakeholders. These variables act as barriers to the province's progress in all aspects of formal education, despite the decentralization of school education through the 18th Amendment in 2010. This study recommends the need to enhance the institutional capacity of the KPK Province in formulating education policies in accordance with the objectives of the 18th Amendment.